A Critical Review of Resistance and Oxidation Mechanisms of Sb-Oxidizing Bacteria for the Bioremediation of Sb(III) Pollution - Deng, Renjian; Chen, Yilin; Deng, Xinpin; Huang, Zhongjie; Zhou, Saijun; Ren, Bozhi; Jin, Guizhong; Hursthouse, Andrew (Frontiers in Microbiology, 2021)
Antimony (Sb) is a priority pollutant in many countries and regions due to its chronic toxicity and potential carcinogenicity. Elevated concentrations of Sb in the environmental originating from mining and other anthropogenic sources are of particular global concern, so the prevention and control of the source of pollution and environment remediation are urgent. It is widely accepted that indigenous microbial play an important role in Sb speciation, mobility, bioavailability and fate in the natural. Especially, antimony oxidizing bacteria can promote the release of antimony from ore deposits to the wider environment. However, it can also oxidise the more toxic antimonite [Sb(Ⅲ)] to the less toxic antimonate [Sb(V)], which is considered as a potentially environmentally friendly and efficient remediation technology for antimony pollution. Therefore, understanding its biological oxidation mechanism has great practical significance to protect environment and human health. This paper reviews studies of the isolation, identification, diversity, Sb(Ⅲ)-resistance mechanisms, Sb(Ⅲ)-oxidation characteristics and mechanisms, and the potential application of Sb-oxidizing bacteria. The aim is to provide a theoretical basis and reference for the diversity and metabolic mechanism of Sb-oxidizing bacteria, the prevention and control of Sb-pollution sources and the application of environment treatment for Sb-pollution.